Penyuluhan Hukum Pencegahan Tindak Pidana Narkotika pada Karang Taruna Desa Purwasari, Kuningan - Andri Hendriawan; Ardiansah Ardiansah; Bilal Abdurrahman; Ganjar Sapta Bayu Perkasa; Ikbal Maolana; Tedi Setiadi; Rifky Sunandi; Suwari Akhmaddhian; Erga Yuhandra (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Teenagers are the future generation of a nation whose mindset and social association must be protected and guided. They can threaten the future of a nation when they are not well directed anymore. Nowadays, teenagers are threatened by drug abuse, an addictive thing which influences immune system, emotion, mindset, and reason. Teenage drug abusers could be increased in annually, therefore an understanding of what lies behind it is needed. One of several factors believed to be the background of drug abused by teenagers is psychological well-being. Based on these problems, legal guidance and legal counseling among adolescents need to be carried out so that adolescents can better understand and have deterrence against drugs. The approach method used in this dedication activity to the community is in the form of legal counseling about preventing drug abuse and a participatory approach, meaning that participants are required to be active in participating throughout the activity.